+0  
 
0
184
1
avatar
(4+1i) * (3-5i)

It says that becomes 17 - 17i

but how's that possible?

Isn't it like this

(4+1i) * (3-5i)
4 * 3 = 12
4 * (-5i) = -20i
1i * 3 = 3i
1i * (-5i) = -5i

So I get it to

12 - 20i + 3i - 5i = 12 - 18i

Any help is very much appreciated, thanks.
Guest Apr 18, 2012
Sort: 

1+0 Answers

 #1
avatar+3071 
0
[input](4+1i) * (3-5i)[/input]

here is the problem: "1i * (-5i) = -5i"

(4+1i) * (3-5i)
4*3-4*5i+1i*3-(5i*1i)
12-20i+3i-(5i^2)
12-20i+3i-(-5)
12-20i+3i+5
17-17i
admin  Apr 18, 2012

26 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details